Effect of Salmonella on Decomposition of Poultry Litter - Mushtaq, M.; Kasur, H.; Khan, R. A.; Khalid, A.; Iqbal, M. K. (Journal of Scientific Research, 2018)
Chicken litter is a significant source of nutrients for production of crops and to reduce the impact of human pathogens on environment. The physicochemical properties of poultry litter mixture compost was assessed against the maturity and stability indices such as carbon nitrogen ratio (C/N), nitrate (NO3), ammonia (NH3), ash, Cation Exchange Capacity (CEC), Humification Index (HI), Humification Rate (HR) and Degree of Polymerization (DP). The use of Salmonella significantly improves the humification process and physicochemical properties of final compost product are better in comparison to control trial. The most prominent effects was the fast rise in temperature from mesophilic to thermophilic stage was accompanied by an increase in NH4+-N that gradually decrease near the maturation phase. Moreover, the decrease in carbon and nitrogen ratio and increase in DP, CEC, HI, HR, phosphorous and potassium was also observed. A significant correlation was found between the maturity and stability parameters like C: N ratio, cation exchange capacity, humification index, degree of polymerization, humification rate and nitrate. Therefore, it is acclaimed that isolated microorganisms Salmonella from poultry litter promote the stable compost formation.